2019
DOI: 10.1155/2019/3864572
|View full text |Cite
|
Sign up to set email alerts
|

Hemianopia and Features of Bálint Syndrome following Occipital Lobe Hemorrhage: Identification and Patient Understanding Have Aided Functional Improvement Years after Onset

Abstract: Introduction. Cerebral visual impairment (CVI) can present around birth or any time thereafter. Homonymous hemianopia is a common feature. The concept that functional improvement is unattainable augurs against active management. Dorsal stream dysfunction (or Bálint syndrome when severe) results from bilateral posterior parietal dysfunction but may go undetected, especially in children. Case Presentation. At 16 the patient suffered spontaneous left occipital lobe brain hemorrhage from a ruptured arteriovenous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…We assessed visual search performance while study participants interacted with two novel VR-based naturalistic environments as a means to objectively characterize functional vision abilities. The results obtained from this study are consistent with the prominence of higher-order visual processing deficits observed in CVI [ 9 , 12 ] and reports of how individuals with CVI face challenges with selecting and extracting visual information from complex scenes [ 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We assessed visual search performance while study participants interacted with two novel VR-based naturalistic environments as a means to objectively characterize functional vision abilities. The results obtained from this study are consistent with the prominence of higher-order visual processing deficits observed in CVI [ 9 , 12 ] and reports of how individuals with CVI face challenges with selecting and extracting visual information from complex scenes [ 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with clinical accounts [ 12 , 13 , 14 , 15 ], we hypothesized that CVI participants would show an overall impairment in search performance as indexed by multiple behavioral outcome measures (including success rate and reaction time) as compared to age-matched controls with neurotypical development. Further, we hypothesized that as a group, individuals with CVI would show greater impairment with increasing task demands associated with scene complexity.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Even in the case where visual acuity and visual field functions are within normal range, deficits with higher order visuospatial processing (including the perception of complex motion) are also frequently observed which can have a profound impact on an individual’s functioning and independence ( Dutton et al, 2006 , Boot et al, 2010 , Dutton, 2013 ). Indeed, individuals with CVI often report feeling overwhelmed in crowded environments, and have difficulty walking down stairs or following the flow of moving traffic ( Lam et al, 2010 , McDowell and Dutton, 2019 ). These visual impairments are thought to be linked to the timing, location, and severity of the underlying neurological injury ( Anderson et al, 2011 ) that affect the development of key visual processing networks within the brain ( Volpe, 2009 ).…”
Section: Introductionmentioning
confidence: 99%